2013
DOI: 10.1155/2013/810508
|View full text |Cite
|
Sign up to set email alerts
|

Thermo Elastic-Plastic Analysis of Rotating Functionally Graded Stainless Steel Composite Cylinder under Internal and External Pressure Using Finite Difference Method

Abstract: The thermal elastic-plastic stresses have been investigated for a rotating functionally graded stainless steel composite cylinder under internal and external pressure with general nonlinear strain hardening law and von Mises' yield criterion using finite difference method. The modulus of elasticity in the rotating cylinder varies radially according to power law and the temperature distribution satisfies Laplace heat equation in radial direction. From the analysis, we can conclude that cylinder made of function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…where p j denotes a plastic strain component; as frequently presumed for cylindrical FGM-devices, Poisson's ratio is considered as constant (see, e.g., [13], Sharma and Yadav [40], Nejad and Fatehi [41]). As a matter of course, in a virgin elastic material p j ¼ 0: For the FGM-hub, it is presupposed that E, a; and q-and also the uniaxial yield limit r y and the thermal conductivity k-depend on the radial coordinate by a power law [13,41].…”
Section: Governing Equationsmentioning
confidence: 99%
“…where p j denotes a plastic strain component; as frequently presumed for cylindrical FGM-devices, Poisson's ratio is considered as constant (see, e.g., [13], Sharma and Yadav [40], Nejad and Fatehi [41]). As a matter of course, in a virgin elastic material p j ¼ 0: For the FGM-hub, it is presupposed that E, a; and q-and also the uniaxial yield limit r y and the thermal conductivity k-depend on the radial coordinate by a power law [13,41].…”
Section: Governing Equationsmentioning
confidence: 99%
“…Next, for the FGM the dependence of E and α on the radial coordinate must be specified: As was already mentioned in the Introduction, power laws are presumed (e.g. ). The basic grading law is however not postulated for the volume fractions of the constituents, but for the modulus of elasticity, and the dependence of the other physical quantities on r is then derived by the rule of mixture ; this approach allows to find a closed‐form solution of the differential equations .…”
Section: Statement Of the Problem Governing Equations And Temperatumentioning
confidence: 99%
“…For the sake of completeness, it shall be mentioned that there also exist studies of the related problems of thermally loaded FGM‐hollow cylinders (e.g. ) and thick‐walled FGM‐shells loaded mechanically only (e.g. ).…”
Section: Introductionmentioning
confidence: 99%
“…Nezad et al [3] determined stresses in thick functionally graded shell having exponentially variable properties subjected to pressure and concluded that non-homogeneity plays significant role on displacement and stress distribution. Sharma et al [4] obtained the numerical solution for thermal elastic-plastic stresses in a functionally graded stainless steel composite cylinder with nonlinear strain hardening and Von-Mises' yield criterion using finite difference method and concluded that cylinder made of functionally graded stainless steel composite material with variable thickness and variable density under thermal loading is better choice of the design as compared to homogeneous cylinder. All these authors adopt the classical approach to investigate the stresses using the assumption of yield criterion, Norton's law.…”
Section: Introductionmentioning
confidence: 99%